1988
DOI: 10.1016/0378-5122(88)90117-x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of regional bone measurements in patients with osteoporotic fractures of the spine and distal forearm

Abstract: Bone mineral mass was measured in normal subjects and osteoporotic patients at two forearm sites (proximal and distal of the 8 mm site between the two forearm bones) by single photon absorptiometry and in the spine and whole body by dual photon absorptiometry. There were no signs of preferential low spinal bone mass in 28 patients with vertebral fractures. Their bone mass was at all sites 26% to 37% lower than the premenopausal mean value and 7% to 13% lower than in age-matched normal women. In 45 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Similar results were found in comparisons of QCT with SPA in 225 postmenopausal women (108 with vertebral fractures) (Nordin 1987) and in comparisons of DPA with SPA in 90 postmenopausal women (18 with vertebral fractures) (Mazess 1984). Other studies with small numbers of vertebral fracture patients have found no significant advantage of DPA over SPA (Nilas 1987, Grubb 1984. In a population-based study of 1,018 Japanese-American women, however, found better agreement between DPA and 0s calcis measurements and concluded that 0s calcis measurements performed as well as DPA of the lumbar spine in determining bone mass and predicting vertebral fracture risk.…”
Section: (C) Bone Mass Of the Vertebrae Can Be Measured Accuratelymentioning
confidence: 86%
“…Similar results were found in comparisons of QCT with SPA in 225 postmenopausal women (108 with vertebral fractures) (Nordin 1987) and in comparisons of DPA with SPA in 90 postmenopausal women (18 with vertebral fractures) (Mazess 1984). Other studies with small numbers of vertebral fracture patients have found no significant advantage of DPA over SPA (Nilas 1987, Grubb 1984. In a population-based study of 1,018 Japanese-American women, however, found better agreement between DPA and 0s calcis measurements and concluded that 0s calcis measurements performed as well as DPA of the lumbar spine in determining bone mass and predicting vertebral fracture risk.…”
Section: (C) Bone Mass Of the Vertebrae Can Be Measured Accuratelymentioning
confidence: 86%
“…Regional specificity may account for the variable magnitudes found in the age-related bone loss [Seeman and Martin. 1989] of vertebrae and upper femoral extremity although other studies seem to indicate that bone loss form all parts of the skeleton develops in a similar way [Nilas et al, 1987]. Our explanations for the moderate correlation between skin fold thickness and lumbar BMD include the presence of osteophytes, spondylo-osteoarthritic changes and/or cal cified aorta in the region of interest automatically defined by the software and taken into account for lumbar BMD measurement.…”
Section: -42mentioning
confidence: 78%
“…It has since become apparent that variations in the fat content of the forearm may be a significant source of error, particularly in longitudinal studies (Need, Horowitz, Walker, Chatterton, Chapman and Nordin 1989;Nilas, Podenphant, Riis, Gotfiedsen and Christiansen 1987). We have therefore established normal ranges for fat-corrected forearm bone mineral content and density in premenopausal women.…”
Section: Introductionmentioning
confidence: 95%